COPING WITH LANGUAGE ANXIETY OF SECOND LANGUAGE USERS: A PSYCHOLOGICAL APPROACH - Syahruddin Mahmud; Adi Suryana (Faculty of Teacher Training and Education, Universitas Sriwijaya, 2015)
Abstract: Language learner anxiety requires appropriate approach. This article proposes two ways approaches to redeem the language learner level of anxiety namely learner centre solution and classroom setting. In some respects, the best solution to cope the learners’ anxiety is by considering holistic approach by looking at both learners’ personal factor and classroom management. It is suggested that language teachers should learn not only about teaching materials but also psychology of the students and class psychology. Keywords: Language user, anxiety, learner solution, class management